La enseñanza de la ética profesional en los estudios universitarios - Agejas, José Ángel; Parada, José Luis; Oliver, Isaac (Revista Complutense de Educación, 2007)
The teaching of professional ethics in University studies is not only a demand that results from social request, but also from the need of curricula renewal and University’s nature of knowledge. After a brief exposition of the status quaestionis in the adaptation of University studies to social demand, the own moral nature –although not specific– of college education is analysed. As a request resulting from this way of being, it develops the way in which university curriculum, accordins to the guidelines of the Bologna Reform, can integrate professional’s own values, abilities and skills in relation to the specific contents of each field of University’s nature of knowledge. Finally, given the sensible character of ethical knowledge, some didactic guidelines for the design and integration of deontology as a University subject are proposed.